2022
DOI: 10.2147/opth.s395577
|View full text |Cite
|
Sign up to set email alerts
|

Brolucizumab in Neovascular Age-Related Macular Degeneration – Indian Real-World Experience: The BRAILLE Study – Fifty-Two-Week Outcomes

Abstract: Purpose To report the 52-week real-world efficacy and safety outcomes of brolucizumab therapy for neovascular age-related macular degeneration (nAMD) in Indian eyes. Patients and Methods A retrospective, multicentre chart analysis of 82 eyes of 82 patients with nAMD (switch therapy: 65 eyes; treatment-naïve: 17 eyes) with 52-week follow-up data was performed. Pro-re-nata re-treatment was offered based on visual and tomographic criteria. Changes in best-corrected visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This study's treatment interval significantly extended from the first to the last interval at 12 months (from 6.15 ± 2.40 to 6.87 ± 2.92, p = 0.045). Several studies have reported the efficacy of brolucizumab for refractory exudative AMD in short-term results in the real-world [41,49,[56][57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…This study's treatment interval significantly extended from the first to the last interval at 12 months (from 6.15 ± 2.40 to 6.87 ± 2.92, p = 0.045). Several studies have reported the efficacy of brolucizumab for refractory exudative AMD in short-term results in the real-world [41,49,[56][57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…They also decided to retreat them with another type of anti-VEGF because of exudative recurrency but they do not report the delay of when they decided to retreat and how the evolution was monthly after retreatment. In their article, Chakraborty et al [20] retreated by IVI of an anti-VEGF only one of their three pa-tients who presented mild intraocular inflammation secondary do brolucizumab with ranibizumab. After that, the patient did not show any inflammatory recurrence but they did not report the delay between the adverse effect of brolucizumab and the retreatment by brolucizumab.…”
Section: Discussionmentioning
confidence: 99%
“… 37 The current study findings were also consistent with the BRAILLE study conducted in Indian patients over 52 weeks wherein brolucizumab demonstrated significant improvement in BCVA with significant reductions in CST, SRF, and IRF. 38 …”
Section: Discussionmentioning
confidence: 99%